Goods or food? Plantation and counterplantation in late colonialism in Mozambique (TEL Tempo, Espaço e Linguagem, 2024)
Crops in Mozambique competed for land with increasing intensity in the mid-20th century. Portuguese colonialism operated towards the implementation of monocultures in order to supply the economy of the metropolis amid anti-colonial pressures. Meanwhile, plants that had long been used by local communities, such as cashews, peanuts and cassava – brought from South America – had their nutritional and symbolic relevance preserved in efforts against capitalist plantation hegemony.